2012
DOI: 10.1103/physrevlett.108.094101
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of Synchronization Clusters in Homogenous Neuronal Ensembles Induced by Noise and Interaction Delays

Abstract: Spontaneous formation of clusters of synchronized spiking in a structureless ensemble of equal stochastically perturbed excitable neurons with delayed coupling is demonstrated for the first time. The effect is a consequence of a subtle interplay between interaction delays, noise and the excitable character of a single neuron. Dependence of the cluster properties on the time-lag, noise intensity and the synaptic strength is investigated.Collective behavior in large ensembles of physiological and inorganic syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…The phenomenon of enhanced coherence produced by optimal noise has been also described in theoretical models of neurons (Casado, 1997; Neiman et al, 1997; Pikovsky and Kurths, 1997; Lee et al, 1998; Wang et al, 2000; Zhong and Xin, 2000; McMillen and Kopell, 2003; Kreuz et al, 2006; Torcini et al, 2007; Li and Gao, 2008; Guo and Li, 2009; Jiang and Ma, 2009; Franović et al, 2012; Gao and Wang, 2012; Men et al, 2012) and experimentally in physical systems (Lih et al, 1998; Postnov et al, 1998; Giacomelli et al, 2000; Zhong and Xin, 2000, 2001a,b; Calvo et al, 2001; Zhong et al, 2001; Kortlüke et al, 2002; Li and Li, 2003, 2004a,b,c, 2006a,b; Bahar and Moss, 2004; Wang et al, 2010; Xin and Hou, 2006; Perc, 2007; Ermentrout et al, 2008; Li et al, 2008; Perc et al, 2008; Shi and Lang, 2009; Shi and Luo, 2010). It has been experimentally shown that the SR is related to increased local (within one area) and long-range (between different areas) synchrony.…”
Section: Introductionmentioning
confidence: 88%
“…The phenomenon of enhanced coherence produced by optimal noise has been also described in theoretical models of neurons (Casado, 1997; Neiman et al, 1997; Pikovsky and Kurths, 1997; Lee et al, 1998; Wang et al, 2000; Zhong and Xin, 2000; McMillen and Kopell, 2003; Kreuz et al, 2006; Torcini et al, 2007; Li and Gao, 2008; Guo and Li, 2009; Jiang and Ma, 2009; Franović et al, 2012; Gao and Wang, 2012; Men et al, 2012) and experimentally in physical systems (Lih et al, 1998; Postnov et al, 1998; Giacomelli et al, 2000; Zhong and Xin, 2000, 2001a,b; Calvo et al, 2001; Zhong et al, 2001; Kortlüke et al, 2002; Li and Li, 2003, 2004a,b,c, 2006a,b; Bahar and Moss, 2004; Wang et al, 2010; Xin and Hou, 2006; Perc, 2007; Ermentrout et al, 2008; Li et al, 2008; Perc et al, 2008; Shi and Lang, 2009; Shi and Luo, 2010). It has been experimentally shown that the SR is related to increased local (within one area) and long-range (between different areas) synchrony.…”
Section: Introductionmentioning
confidence: 88%
“…Apart from the increase of fluctuation amplitudes, enhancing D may give rise to the transition from the stochastically stable FP to the noise-induced spiking. The latter can appear as nearly periodic or irregular depending on c, τ , and D. It is known that in systems of excitable units subjected to D and τ , the length of interspike intervals (ISIs) is influenced by the competition between two characteristic time scales [6,7]. One is set by the self-oscillation "period" T 0 (D) obtained for τ = 0, whereas the other is adjusted with τ .…”
Section: A Background On the Exact Systemmentioning
confidence: 99%
“…The interplay of noise and delays becomes especially intricate if the units making up the system are not self-oscillating, but excitable [5]. For such a setup, the local and collective dynamics rest on the competition between the delay-driven and the noise-induced oscillation modes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This refers to a sequence of local bifurcations under variation of D, τ in and g in , which can be used to highlight the parameter domains giving rise to oscillatory states or those that lead to the amplitude death [36]. In addition, the MF model of an isolated ensemble has also been found to reflect the global bifurcation imminent to the onset of clustering in the exact system [44]. Before proceeding to the main results, several brief remarks on the applied numerical integration schemes are in order.…”
Section: B Background and The Formulation Of The Mf Approximationmentioning
confidence: 99%